Longitudinal study of thyroid function in Down's syndrome in the first two decades. Issue 6 (20th May 2005) - Gibson, P A; Newton, R W; Selby, K; Price, D A; Leyland, K; Addison, G M
Abstract : Aims and Methods: Thyroid function tests were initially carried out on 122 children with Down's syndrome aged 6–14 years and then repeated four to six years later in 103 adolescents (85% of the group of 122) when they were aged 10–20 years (median 14.4 years). At the second test two were hypothyroid and two with isolated raised thyroid stimulating hormone (IR-TSH) were receiving thyroxine. Results: At the first test there were 98 (80%) euthyroid children: 83 were retested and four (5%) had IR-TSH. At the first test 24 had IR-TSH: 20 were retested and 14 (70%) had become normal. Seventeen with IR-TSH on initial testing had a thyrotrophin releasing hormone test within three months; TSH had become normal in eight (47%) of these children. There was no association between reported clinical symptoms and IR-TSH, but there were clear symptoms in one of the two with definite hypothyroidism. Conclusions: The likelihood ratio for a positive result on second testing when raised TSH and positive antibody status on first testing are combined is 20. This suggests initial testing results could be used as a basis to select a subgroup for further testing at say five yearly intervals unless new symptoms emerge in the interim. It also suggests that yearly screening (as recommended by the American Academy of Pediatrics, 2001) is probably not justified in the first 20 years of life.